2005
DOI: 10.1111/j.1365-2648.2004.03302.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived parental efficacy: concept analysis

Abstract: This conceptual analysis has allowed perceived parental efficacy to be distinguished from parental confidence and parental competence. Both nursing and psychology research, practice and education will benefit from a more precise and delineated concept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
162
0
10

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(190 citation statements)
references
References 70 publications
(144 reference statements)
6
162
0
10
Order By: Relevance
“…Unconfident Japanese mothers were less attached to their babies and felt their husbands' help was limited. It has been noted elsewhere that maternal confidence is closely related with self-efficacy, which is a protective mediator of postpartum depression [13]. A recent study in Vietnam revealed a high prevalence of postpartum depression measured by the Edinburgh Postnatal Depression Scale around 1-month postpartum (33% in Vietnam with a cut-off point of 13 or higher [14] versus 18% in Japan with a cut-off point of 9 or higher [15]), arguing for closer consideration of Vietnamese mothers' mental health.…”
Section: Discussionmentioning
confidence: 93%
“…Unconfident Japanese mothers were less attached to their babies and felt their husbands' help was limited. It has been noted elsewhere that maternal confidence is closely related with self-efficacy, which is a protective mediator of postpartum depression [13]. A recent study in Vietnam revealed a high prevalence of postpartum depression measured by the Edinburgh Postnatal Depression Scale around 1-month postpartum (33% in Vietnam with a cut-off point of 13 or higher [14] versus 18% in Japan with a cut-off point of 9 or higher [15]), arguing for closer consideration of Vietnamese mothers' mental health.…”
Section: Discussionmentioning
confidence: 93%
“…Parenting sense of competence is a cognitive and emotional construct that consists in the judgments that parents hold about their abilities to perform parenthood-related tasks (Farkas & Valdés, 2010;Jones & Prinz, 2005;Montigny & Lacharité, 2005). It also encompasses parents' beliefs about their ability to influence their children' s development in a positive manner (Ardelt & Eccles, 2001) and the satisfaction derived from the parenting role (Johnston & Mash, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Their mean age was 19 (in a range of [13][14][15][16][17][18][19][20][21][22][23][24].The mean age of their children was 6 months (in a range of 0.2-12).They came from socioeconomic brackets 1 (29%), 2 (52%) and 3 (19%).The most common occupation was housewife (87%).…”
Section: Resultsmentioning
confidence: 99%